Plato and democracy’s ambiguous beauty (ii): philosophy and power - Sá, Alexandre Franco de (Revista Archai, 2017)
The opposition between philosophy and philodoxy in Plato’s thought seems to suggest that philosophy could be taken, at first sight, as the sketch of an alternative political project to democracy. If democracy lies on the crowd’s power, and the opinions (doxai) current among it, philosophy would rest on philosopher’s power, i.e. on the power of those who possess the “art of ruling”. The present paper focuses on the insufficiency of this first approach and questions the relationship between philosophy and power. We will argue that Plato places this relationship on a twofold notion. On the one hand, the notion that if philosophy would have enough power to oppose the democratic city, this power, consisting in absolute tyranny, would mean the corruption of philosophy as such. On the other hand, the notion that if philosophy rest exclusively on its arguments with no relationship with power whatsoever, it would be simply powerless and have no place within the polis.